2021
DOI: 10.1177/00219983211031633
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microfillers addition on the flexural properties of carbon fiber reinforced phenolic composites

Abstract: The effects of microfiller addition on the flexural properties of carbon fiber reinforced phenolic (CFRP) matrix composites were investigated. The CFRP was produced using colloidal silica and silicon carbide (SiC) microfillers, 2 D woven carbon fibers, and two variants of phenolic resole (HRJ-15881 and SP-6877). The resins have the same phenol and solid content but differ in their viscosities and HCHO (formaldehyde) content. The weight fractions of microfillers incorporated into the phenolic matrix are 0.5 wt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The aerospace and automotive industries require a material that has a combination of unique properties including light weight, hardness, strength, stiffness, and wear resistance. Composites, which are fabricated by combining two or more different components, are often the only materials that can meet the diverse and demanding requirements of modern engineering applications [8,9]. Pank and Jackson [10] reported that MMCs with capabilities to withstand high temperature offer unique application for airspace industries by providing high strength and high modulus fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The aerospace and automotive industries require a material that has a combination of unique properties including light weight, hardness, strength, stiffness, and wear resistance. Composites, which are fabricated by combining two or more different components, are often the only materials that can meet the diverse and demanding requirements of modern engineering applications [8,9]. Pank and Jackson [10] reported that MMCs with capabilities to withstand high temperature offer unique application for airspace industries by providing high strength and high modulus fibers.…”
Section: Introductionmentioning
confidence: 99%
“…PEG has long molecular chains tend to disrupt the mutual a raction between individual microfiller particles, thereb moting their uniform dispersion in the phenolic resins [37,38]. A detailed description of the dispersion of colloidal silica (CS) and SiC microfil the phenolic resins can be found in the work of Abdulganiyu et al [54]. To provide f context, CS was mixed with PEG in a ratio of 2:1 to form a shear-thickening fluid By shear thickening, we mean an increase in viscosity with increasing rate of shear during mechanical deformation [55].…”
Section: Methodsmentioning
confidence: 99%
“…Phenolic is also one of the essential ingredients used in friction material as it is a strong binder, and high-strength binders improve the overall friction materials’ performance [ 9 ]. There is literature that discusses the improvement of phenolic’s properties when reinforced with fillers such as alumina, calcium carbonate, silicon carbide, talc, copper, carbon black, graphite, and CNTs [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%